Abundance of Indian Ocean humpback dolphins (Sousa plumbea) along the Garden Route of South Africa - W. Chris Oosthuizen; Stephen P. Kirkman; Danielle S. Conry; O. Alejandra Vargas-Fonseca; Vic Cockcroft; Gareth Greenwood; Pierre A. Pistorius (Frontiers in Marine Science, 2026)
Human development is placing growing pressure on coastal ecosystems worldwide. Coastal dolphins are consequently exposed to a range of anthropogenic threats, yet for many species, limited knowledge of population size and dynamics hinders effective conservation planning. Four species of humpback dolphin ( Sousa spp.) inhabit shallow coastal waters globally, and all are threatened by human activities. Along the South African coast, the endangered Indian Ocean humpback dolphin ( Sousa plumbea ) occurs in a small, declining population whose abundance is thought to be fewer than 500 individuals. Here, we estimate the abundance and group structure of this species along the Garden Route on South Africa’s south coast. We conducted photo-identification surveys from March 2014 to June 2015 and fitted a Bayesian open-population (Jolly-Seber) model to encounter histories of 65 identified individuals. Dolphins were encountered most consistently in the west of the study area, particularly inside the Goukamma marine protected area, and never in large groups. We estimated that approximately 89 individuals occurred in the study area over the survey period, representing around one-fifth of the latest abundance estimate for the species in South Africa. We also analyzed intermittently collected photo-identification data from Plettenberg Bay, a subset of the study area, to evaluate temporal changes in local abundance. This suggested a decline in abundance over comparable 12-month periods, from a posterior mean of 112 individuals in 2002/03 to approximately 60–70 individuals in 2012/13 and 2014/15, consistent with declines reported elsewhere across the species’ range. This study underscores the importance of the Garden Route region for conservation of this species and provides a valuable baseline against which future population change can be assessed.

Perceived costs as drivers of wildlife management preferences in rural Tanzanian communities - Christian Kiffner; Justin Raycraft; Reilly Becchina; Danielle Bettermann; Stephen Koester; Elana Kriegel; Kiana Lindsay; Edwin Maingo Ole; Emily Ramirez; Bryan Spizuco; Neil H. Carter (Conservation Biology, 2026)
Effectively managing human–wildlife interactions is crucial for fostering coexistence on shared landscapes. Management options are most effective when aligned with the preferences of people directly affected by wildlife, yet little is known about how socioecological factors influence these preferences. Integrating responses from 680 rural residents of northern Tanzania and remotely sensed data, we parameterized a Bayesian hierarchical model to test predictions of the hazard‐acceptance model. We estimated how perceived costs and benefits, distance to protected areas, and the human footprint index mediate preferences for managing (preventing damage, compensating damage, reducing populations, and doing nothing) interactions with herbivore (elephant, giraffe, buffalo, zebra, wildebeest, and impala) and carnivore (lion, hyena, leopard, cheetah, honey badger, and jackal) species. Most respondents preferred management options that supported coexistence: prevention (41.9%), no management (38.0%), and compensation (11.1%). In contrast, population reduction (9.0%) was least preferred but more frequently selected for carnivores (13.4%) than herbivores (5.3%). Perceived costs strongly influenced management preferences. Respondents perceiving tangible costs were more likely to prefer prevention (posterior mean: 0.57 [95% credible interval 0.00 to 0.99]) over compensation (0.07 [0.00 to 0.66]) or population reduction (0.16 [0.00 to 0.87]), whereas those not perceiving costs leaned toward no management (0.40 [−0.74 to 1.78]). Though perceived benefits were less influential than costs, respondents associating species with intangible (0.10 [0.00 to 0.74]) or tourism benefits (0.06 [0.00 to 0.63]) were less likely to support population reduction than those perceiving no benefits (0.12 [0.00 to 0.82]). Distance to protected areas and the human footprint index had weaker, inconsistent effects, but random intercepts indicated substantial village–village variation in preferred management options. Our results suggest that conservation strategies should primarily address wildlife‐related costs and foster coexistence by more equitably distributing benefits. A possible strategy could include investing tourism revenues into comanaged, locally tailored damage prevention measures.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Improved forecasting of cotton canopy temperature for irrigation scheduling - Stephen Rogers; Huidong Jin; Rose Roche; Danielle A. Way (Agricultural and Forest Meteorology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Melanin and methylation: coat color is linked to directional epigenetic shifts in Alaskan wolves - Elizabeth L. Sheldon; Gretchen H. Roffler; M. E. Lauer; Daniella Ray; Danielle Dawkins; Matthew Stephen Broderick; Aaron W. Schrey (Mammal Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Significant mortality of old trees across a dry forest landscape, Oregon, USA - James D. Johnston; Paige N. Stephens; Micah R. Schmidt; Sean M.A. Jeronimo; Amanda E. Brackett; Amarina E. Wuenschel; Danielle E.M. Ulrich; Riley H. Paine; Lou F. Duloisy; Skye M. Greenler; Andrew J. Larson; Derek J. Churchill (Forest Ecology and Management, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

Variable social-ecological indicators across a Tanzanian protected area network - Juliette Vallin; Justin Raycraft; Danielle Bettermann; John Kioko; Bernard M. Kissui; Stephen Koester; Kiana Lindsay; Edwin Maingo Ole; Emily Ramirez; Bryan Spizuco; Jacqueline Loos; Christian Kiffner (Biological Conservation, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Lake shape and the characteristics of migration behavior modify Atlantic salmon smolt migration success through lakes - Matthew Newton; Joseph McCallum; Hannele M. Honkanen; Alastair Stephen; Jessie M. Lilly; Danielle L. Orrell; Amy Green; Louise Chavarie; Jessica R. Rodger; Colin E. Adams (Journal of Fish Biology, 2025)
Migration is a high‐risk behavior. For the Atlantic salmon, Salmo salar , migrating from its river nursery area to marine feeding grounds, the magnitude of risk varies with habitat type. Passage through lakes, in particular, is associated with low rates of migration success. Downstream migrating salmon smolts are rheotactic when migrating in rivers, but lakes typically provide poorer directional currents for migrating salmon. In this study we tested if, in the absence of clear navigational cues in lakes, Atlantic salmon smolts switch to a random search strategy to find the outflowing river. We constructed random search simulations to test if lake basin shape has an effect on migration success. We also compared simulated migration characteristics with migrations of salmon smolts through five real lakes for which there are telemetry data for migrating salmon. Correlated random walk simulations showed that a random search strategy could be successful for all lake shapes tested but was more successful in curved (round and elliptical) than rectangular basin shapes. Rectangular basins with the migration start and stop points at the ends of the lake had a higher success than those where these points were perpendicular to the axis of the lake. In general, a random walk model predicted the migration success rate of fish tracked through real lakes. However, for two lakes the simulated migration success exceeded that of actual success, suggesting that fish passing through these lakes were not adopting a random search strategy. We speculate that this is the result of either conflicting navigational cues which inhibit smolts from finding the lake outlet or that they temporarily suspend migration (e.g., to feed). Modelling predicted that for small lakes, directional swimming in short steps (ca. 100 m) followed by turns with very low variation from the direction of travel resulted in the highest migration success. For larger lakes, longer step lengths but also with low turn variation (simulated turning angle drawn from distributions of standard deviation 2 ° and 5 ° around a mean of 0 ° ) resulted in the highest migration success. We conclude that navigation in downstream migrating salmon smolts switches from rheotaxis in rivers to a random search tactic in lakes except where residual flow cues in some lakes prevent this, at times resulting in suboptimal navigation outcomes.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Genetic Monitoring of a Lethal Control Programme for Wild Canids With Complex Mating Strategies - Thomas A. A. Prowse; Aysegul Birand; Danielle Stephens; Andrew P. Woolnough (Molecular Ecology, 2025)
Although mammalian carnivores are ecologically important, they also drive human–wildlife conflicts. Managing carnivores using lethal control is controversial, in part because the impact of control effort is often uncertain due to limited abundance monitoring. We used an Australian metapopulation of wild dogs as a model system to investigate the feasibility of monitoring effective population size () to detect reductions in census population size () following control. Based on microsatellite data collected over an 11‐year period, we parameterised an individual‐based spatial population model for wild dogs that integrated demography, genetics, random or hierarchical mating, dispersal between subpopulations and compensatory immigration. and trajectories were simulated under different proportional culling rates and genetic sampling regimes. We also used simulations without culling as null models to define 95% critical values for assessing the significance of empirical changes in over time. We concluded there were significant reductions (39%–62%) in in each subpopulation of the wild dog metapopulation, mostly likely due to control. In simulations assuming a hierarchical rather than random mating system, the impact of control on was weakened because reproduction by subordinate individuals increased as dominant individuals were removed, yet reduced following culling. Sensitivity analyses demonstrated that becomes an unreliable proxy of when compensatory immigration is strong and compensatory reproduction is weak, in which case can increase following culling due to the immigration of new genotypes. Nonetheless, our results suggest can provide information about wild dog over sufficiently short timescales to inform management.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Warming reduces trophic diversity in high‐latitude food webs - Michelle C. Jackson; Eoin J. O'Gorman; Bruno Gallo; Sarah F. Harpenslager; Kate Randall; Danielle N. Harris; Hannah Prentice; Mark Trimmer; Ian Sanders; Alex J. Dumbrell; Tom C. Cameron; Katrin Layer‐Dobra; et al. (Global Change Biology, 2024)
The physical effects of climate warming have been well documented, but the biological responses are far less well known, especially at the ecosystem level and at large (intercontinental) scales. Global warming over the next century is generally predicted to reduce food web complexity, but this is rarely tested empirically due to the dearth of studies isolating the effects of temperature on complex natural food webs. To overcome this obstacle, we used ‘natural experiments’ across 14 streams in Iceland and Russia, with natural warming of up to 20°C above the coldest stream in each high‐latitude region, where anthropogenic warming is predicted to be especially rapid. Using biomass‐weighted stable isotope data, we found that community isotopic divergence (a universal, taxon‐free measure of trophic diversity) was consistently lower in warmer streams. We also found a clear shift towards greater assimilation of autochthonous carbon, which was driven by increasing dominance of herbivores but without a concomitant increase in algal stocks. Overall, our results support the prediction that higher temperatures will simplify high‐latitude freshwater ecosystems and provide the first mechanistic glimpses of how warming alters energy transfer through food webs at intercontinental scales.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Isolation, small population size, and management influence inbreeding and reduced genetic variation in K’gari dingoes - Susan M. Miller; Linda Behrendorff; Benjamin L. Allen; Rose L. Andrew; Guy Ballard; J. William O. Ballard; Kylie M. Cairns; Gabriel C. Conroy; Peter J. S. Fleming; Catherine E. Grueber; Jane Oakey; Deane A. Smith; et al. (Conservation Genetics, 2024)
Small island populations are vulnerable to genetic decline via demographic and environmental stochasticity. In the absence of immigration, founder effects, inbreeding and genetic drift are likely to contribute to local extinction risk. Management actions may also have a greater impact on small, closed populations. The demographic and social characteristics of a species can, however, delay the impact of threats. K’gari, a ~ 1 660 km 2 island off the Australian east coast and UNESCO World Heritage Site (Fraser Island 1842–2023), supports an isolated population of approximately 70–200 dingoes that represent an ideal opportunity to explore the small island paradigm. To examine temporal and spatial patterns of genetic diversity in this population we analysed single nucleotide polymorphism (SNP) genotype data (72 454 SNPS) for 112 K’gari dingoes collected over a 25-year period (1996 to 2020). Genetic diversity was lower in K’gari dingoes than mainland dingoes at the earliest time point in our study and declined significantly following a management cull in 2001. We did not find any spatial genetic patterns on the island, suggesting high levels of genetic connectivity between socially discrete packs. This connectivity, combined with the social structure and behaviour of dingoes, may act in concert to buffer the population from the impacts of genetic drift in the short term. Nevertheless, a general decline in genetic variation via inbreeding and drift has occurred over the past 20 years which we suggest should be considered in any future management planning for the population. Monitoring patterns of genetic variation, together with a clearer understanding of the social ecology of K’gari dingoes, will aid in the development of measurable genetic targets set over ecologically meaningful timelines, and help ensure continued survival of this culturally important population.

Built‐environment stocks in the context of a master‐planned city: A case study of Chandigarh, India - William Mihkelson; Hadi Arbabi; Stephen Hincks; Danielle Densley Tingley (Journal of Industrial Ecology, 2024)
Construction materials accumulate in the built environment forming material stocks (MS) of buildings and infrastructure, providing various services to society that result in a nexus of human development and environmental impact. Meanwhile, unprecedented urbanization in the Global South is set to put significant demand on the resources required to ensure adequate standards of living in new and existing urban areas. This is particularly important within India; however, no study has yet explored MS within cities in India or within master‐planned urban areas designed to accommodate urbanization and a high standard of living. The present study begins to fill these gaps and aims to investigate patterns of built‐environment MS accumulation in Chandigarh, an exceptionally quickly developed city master planned to ensure universally high standards of living through a unique urban form. We adopt a bottom‐up approach to quantify the residential building and road MS at the city and sub‐city scale. The results reveal that the master plan, while enabling high standards of living, has resulted in a relative accumulation of road‐to‐building stock that is significantly larger than in other cities. This is shown to be environmentally detrimental as future urban development is limited and promotes the demolition of existing stocks, whose composition severely limits their potential as secondary resources. The study therefore provides empirical evidence to support the integration of material stock assessments into urban planning and development to ensure resource‐efficient provisioning of key services.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Design of a randomized, placebo-controlled study evaluating efficacy and safety of a cancer preventative vaccine in dogs - Jenna H. Burton; Stephen Albert Johnston; David M. Vail; Jens C. Eickhoff; Kathryn F. Sykes; Justin R. Brown; Luhui Shen; Ana Gervassi; Rodney L. Page; Jennifer L. Willcox; Sami Al-Nadaf; Amanda L. Willis; et al. (Veterinary Immunology and Immunopathology, 2024)

Anoxia begets anoxia: A positive feedback to the deoxygenation of temperate lakes - Abigail S. L. Lewis; Maximilian P. Lau; Stephen F. Jane; Kevin C. Rose; Yaron Be'eri‐Shlevin; Sarah H. Burnet; François Clayer; Heidrun Feuchtmayr; Hans‐Peter Grossart; Dexter W. Howard; Heather Mariash; Jordi Delgado Martin; et al. (Global Change Biology, 2024)
Declining oxygen concentrations in the deep waters of lakes worldwide pose a pressing environmental and societal challenge. Existing theory suggests that low deep‐water dissolved oxygen (DO) concentrations could trigger a positive feedback through which anoxia (i.e., very low DO) during a given summer begets increasingly severe occurrences of anoxia in following summers. Specifically, anoxic conditions can promote nutrient release from sediments, thereby stimulating phytoplankton growth, and subsequent phytoplankton decomposition can fuel heterotrophic respiration, resulting in increased spatial extent and duration of anoxia. However, while the individual relationships in this feedback are well established, to our knowledge, there has not been a systematic analysis within or across lakes that simultaneously demonstrates all of the mechanisms necessary to produce a positive feedback that reinforces anoxia. Here, we compiled data from 656 widespread temperate lakes and reservoirs to analyze the proposed anoxia begets anoxia feedback. Lakes in the dataset span a broad range of surface area (1–126,909 ha), maximum depth (6–370 m), and morphometry, with a median time‐series duration of 30 years at each lake. Using linear mixed models, we found support for each of the positive feedback relationships between anoxia, phosphorus concentrations, chlorophyll a concentrations, and oxygen demand across the 656‐lake dataset. Likewise, we found further support for these relationships by analyzing time‐series data from individual lakes. Our results indicate that the strength of these feedback relationships may vary with lake‐specific characteristics: For example, we found that surface phosphorus concentrations were more positively associated with chlorophyll a in high‐phosphorus lakes, and oxygen demand had a stronger influence on the extent of anoxia in deep lakes. Taken together, these results support the existence of a positive feedback that could magnify the effects of climate change and other anthropogenic pressures driving the development of anoxia in lakes around the world.

Conservation of skinks in New Zealand cities - Christopher K. Woolley; Stephen Hartley; John G. Innes; Danielle F. Shanahan; Yolanda van Heezik; Deborah J. Wilson; Nicola J. Nelson (Urban Ecosystems, 2023)
Urbanisation dramatically alters ecosystems, disrupting key processes and threatening species persistence. Despite growing knowledge of the impacts of cities on wildlife, particularly for birds and mammals, there remains a paucity of research on how urbanisation impacts other taxa, including reptiles. We examined how urbanisation affects skink communities across multiple New Zealand cities by undertaking pitfall trapping surveys in a range of habitats. Of the 20 endemic species thought to have been present historically in the cities, only four were captured during surveys, Oligosoma aeneum in Hamilton; O. polychroma , O. aeneum , and O. ornatum in Wellington; O. polychroma in Nelson; and O. aff. polychroma Clade 5 in Dunedin. Our results reveal highly variable patterns of occupancy, abundance, and complex associations with key threats and habitat modifications. Sites in Nelson and Wellington were much more likely to record skinks than Hamilton and Dunedin, and modelling showed abundance of O. polychroma was positively related to rat tracking rates when grass cover was low but showed a negative relationship when grass cover was high. O. polychroma body condition was negatively associated with the proportion of urban land cover (built up areas or transport infrastructure). The low number of captures of several species is concerning and long-term monitoring is needed to assess the trajectories of these vulnerable populations. Effective conservation management of urban wildlife requires knowledge of where populations exist and how urban processes affect persistence. For understudied urban-dwelling taxa such as reptiles, the lack of this information may be putting populations at risk.

Closing the gap between science and management of cold‐water refuges in rivers and streams - Francine H. Mejia; Valerie Ouellet; Martin A. Briggs; Stephanie M. Carlson; Roser Casas‐Mulet; Mollie Chapman; Mathias J. Collins; Stephen J. Dugdale; Joseph L. Ebersole; Danielle M. Frechette; Aimee H. Fullerton; Carole‐Anne Gillis; et al. (Global Change Biology, 2023)
Human activities and climate change threaten coldwater organisms in freshwater ecosystems by causing rivers and streams to warm, increasing the intensity and frequency of warm temperature events, and reducing thermal heterogeneity. Cold‐water refuges are discrete patches of relatively cool water that are used by coldwater organisms for thermal relief and short‐term survival. Globally, cohesive management approaches are needed that consider interlinked physical, biological, and social factors of cold‐water refuges. We review current understanding of cold‐water refuges, identify gaps between science and management, and evaluate policies aimed at protecting thermally sensitive species. Existing policies include designating cold‐water habitats, restricting fishing during warm periods, and implementing threshold temperature standards or guidelines. However, these policies are rare and uncoordinated across spatial scales and often do not consider input from Indigenous peoples. We propose that cold‐water refuges be managed as distinct operational landscape units, which provide a social and ecological context that is relevant at the watershed scale. These operational landscape units provide the foundation for an integrated framework that links science and management by (1) mapping and characterizing cold‐water refuges to prioritize management and conservation actions, (2) leveraging existing and new policies, (3) improving coordination across jurisdictions, and (4) implementing adaptive management practices across scales. Our findings show that while there are many opportunities for scientific advancement, the current state of the sciences is sufficient to inform policy and management. Our proposed framework provides a path forward for managing and protecting cold‐water refuges using existing and new policies to protect coldwater organisms in the face of global change.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Detection of human adenovirus F41 in wastewater and its relationship to clinical cases of acute hepatitis of unknown aetiology - Marina I. Reyne; Danielle M. Allen; Ashley Levickas; Pearce Allingham; Jonathan Lock; Arthur Fitzgerald; Cormac McSparron; Behnam F. Nejad; Jennifer McKinley; Andrew Lee; Stephen H. Bell; Joshua Quick; et al. (Science of The Total Environment, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Essential outcomes for COP26 - Pete Smith; Linda Beaumont; Carl J. Bernacchi; Maria Byrne; William Cheung; Richard T. Conant; Francesca Cotrufo; Xiaojuan Feng; Ivan Janssens; Hefin Jones; Miko U. F. Kirschbaum; Kazuhiko Kobayashi; et al. (Global Change Biology, 2022)

Bmi1 Regulates Wnt Signaling in Hematopoietic Stem and Progenitor Cells - Hao Yu; Rui Gao; Sisi Chen; Xicheng Liu; Qiang Wang; Wenjie Cai; Sasidhar Vemula; Aidan C. Fahey; Danielle Henley; Michihiro Kobayashi; Stephen Z. Liu; Zhijian Qian; et al. (Stem Cell Reviews and Reports, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Effects of inescapable stress on responses to social incentive stimuli and modulation by escitalopram - Stephen Daniels; Danielle Lemaire; Thomas Lapointe; Cheryl Limebeer; Linda Parker; Francesco Leri (Psychopharmacology, 2021)

Impacts of light detection and ranging (LiDAR) data organization and unit of analysis on land cover classification - Danielle Beaulne; Georgia Fotopoulos; Stephen C. Lougheed (International Journal of Remote Sensing, 2021)

A lipid normalization model for the analysis of stable isotopes in baleen whale earplugs - Farzaneh Mansouri; Danielle D. Crain; Zach C. Winfield; Richard Sabin; Charles W. Potter; Ren Zhang; Stephen J. Trumble; Sascha Usenko (Marine Mammal Science, 2021)

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Civil disobedience movements such as School Strike for the Climate are raising public awareness of the climate change emergency - Stephen J. Thackeray; Sharon A. Robinson; Pete Smith; Rhea Bruno; Miko U. F. Kirschbaum; Carl Bernacchi; Maria Byrne; William Cheung; M. Francesca Cotrufo; Phillip Gienapp; Sue Hartley; Ivan Janssens; et al. (Global Change Biology, 2020)

The independent effects of nutrient enrichment and pulsed nutrient delivery on a common wetland invader and its native conspecific - Danielle M. Frevola; Stephen M. Hovick (Oecologia, 2019)

Effect of temperature on zooplankton vertical migration velocity - Stefano Simoncelli; Stephen J. Thackeray; Danielle J. Wain (Hydrobiologia, 2019)

On biogenic turbulence production and mixing from vertically migrating zooplankton in lakes - Stefano Simoncelli; Stephen J. Thackeray; Danielle J. Wain (Aquatic Sciences, 2018)

Gene expression profiling reveals deep‐sea coral response to the Deepwater Horizon oil spill - Danielle M. DeLeo; Santiago Herrera; Stephen D. Lengyel; Andrea M. Quattrini; Rob J. Kulathinal; Erik E. Cordes (Molecular Ecology, 2018)
Deep‐sea coral communities are key components of the Gulf of Mexico ecosystem and were adversely affected by the Deepwater Horizon ( DWH ) oil spill. Coral colonies exposed to oil and dispersant exhibited mortality, damage and physiological signatures of stress. Understanding how corals respond to oil and dispersant exposure at the molecular level is important to elucidate the sublethal effects of the DWH disaster and reveal broader patterns of coral stress responses. Gene expression profiles from RNA seq data were compared between corals at an impacted site and from a reference site. A total of 1,439 differentially expressed genes (≥twofold) were shared among impacted Paramuricea biscaya colonies. Genes involved in oxidative stress, immunity, wound repair, tissue regeneration and metabolism of xenobiotics were significantly differentially expressed in impacted corals. Enrichment among the overexpressed genes indicates the corals were enduring high metabolic demands associated with cellular stress responses and repair mechanisms. Underexpression of genes vital to toxin processing also suggests a diminished capacity to cope with environmental stressors. Our results provide evidence that deep‐sea corals exhibited genome‐wide cellular stress responses to oil and dispersant exposure and demonstrate the utility of next‐generation sequencing for monitoring anthropogenic impacts in deep waters. These analyses will facilitate the development of diagnostic markers for oil and dispersant exposure in deep‐sea invertebrates and inform future oil spill response efforts.

Vulnerability of forests of the Midwest and Northeast United States to climate change - Chris Swanston; Leslie A. Brandt; Maria K. Janowiak; Stephen D. Handler; Patricia Butler-Leopold; Louis Iverson; Frank R. Thompson III; Todd A. Ontl; P. Danielle Shannon (Climatic Change, 2018)

Adaptation pathways: ecoregion and land ownership influences on climate adaptation decision-making in forest management - Todd A. Ontl; Chris Swanston; Leslie A. Brandt; Patricia R. Butler; Anthony W. D’Amato; Stephen D. Handler; Maria K. Janowiak; P. Danielle Shannon (Climatic Change, 2018)

Response to varying the nicotine content of cigarettes in vulnerable populations: an initial experimental examination of acute effects - Stephen T. Higgins; Sarah H. Heil; Stacey C. Sigmon; Jennifer W. Tidey; Diann E. Gaalema; Maxine L. Stitzer; Hanna Durand; Janice Y. Bunn; Jeff S. Priest; Christopher A. Arger; Mollie E. Miller; Cecilia L. Bergeria; et al. (Psychopharmacology, 2017)

Mitochondrial defects associated with β-alanine toxicity: relevance to hyper-beta-alaninemia - Aza Shetewy; Kayoko Shimada-Takaura; Danielle Warner; Chian Ju Jong; Abu-Bakr Al Mehdi; Mikhail Alexeyev; Kyoko Takahashi; Stephen W. Schaffer (Molecular and Cellular Biochemistry, 2016)

Importance of Molecular Methods to Determine Whether a Probiotic is the Source of Lactobacillus Bacteremia - Alla Aroutcheva; Julie Auclair; Martin Frappier; Mathieu Millette; Karen Lolans; Danielle de Montigny; Serge Carrière; Stephen Sokalski; William E. Trick; Robert A. Weinstein (Probiotics and Antimicrobial Proteins, 2016)

Corrigendum - Danielle Stephens; Alan N. Wilton; Peter J. S. Fleming; Oliver Berry (Molecular Ecology, 2016)

Death by sex in an Australian icon: a continent‐wide survey reveals extensive hybridization between dingoes and domestic dogs - Danielle Stephens; Alan N. Wilton; Peter J.S. Fleming; Oliver Berry (Molecular Ecology, 2015)
Hybridization between domesticated animals and their wild counterparts can disrupt adaptive gene combinations, reduce genetic diversity, extinguish wild populations and change ecosystem function. The dingo is a free‐ranging dog that is an iconic apex predator and distributed throughout most of mainland Australia. Dingoes readily hybridize with domestic dogs, and in many Australian jurisdictions, distinct management strategies are dictated by hybrid status. Yet, the magnitude and spatial extent of domestic dog–dingo hybridization is poorly characterized. To address this, we performed a continent‐wide analysis of hybridization throughout Australia based on 24 locus microsatellite DNA genotypes from 3637 free‐ranging dogs. Although 46% of all free‐ranging dogs were classified as pure dingoes, all regions exhibited some hybridization, and the magnitude varied substantially. The southeast of Australia was highly admixed, with 99% of animals being hybrids or feral domestic dogs, whereas only 13% of the animals from remote central Australia were hybrids. Almost all free‐ranging dogs had some dingo ancestry, indicating that domestic dogs could have poor survivorship in nonurban Australian environments. Overall, wild pure dingoes remain the dominant predator over most of Australia, but the speed and extent to which hybridization has occurred in the approximately 220 years since the first introduction of domestic dogs indicate that the process may soon threaten the persistence of pure dingoes.

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

A Middle Devensian woolly rhinoceros ( Coelodonta antiquitatis ) from Whitemoor Haye Quarry, Staffordshire (UK): palaeoenvironmental context and significance - Danielle Schreve; Andy Howard; Andrew Currant; Stephen Brooks; Simon Buteux; Russell Coope; Barnaby Crocker; Michael Field; Malcolm Greenwood; James Greig; Phillip Toms (Journal of Quaternary Science, 2013)
This paper reports the discovery of a rare partial skeleton of a woolly rhinoceros ( Coelodonta antiquitatis Blumenbach, 1799) and associated fauna from a low Pleistocene terrace of the River Tame at Whitemoor Haye, Staffordshire, UK. A study of the sedimentary deposits around the rhino skeleton and associated organic‐rich clasts containing pollen, plant and arthropod remains suggests that the animal was rapidly buried on a braided river floodplain surrounded by a predominantly treeless, herb‐rich grassland. Highlights of the study include the oldest British chironomid record published to date and novel analysis of the palaeoflow regime using caddisfly remains. For the first time, comparative calculations of coleopteran and chironomid palaeotemperatures have been made on the same samples, suggesting a mean July temperature of 8–11 °C and a mean December temperature of between −22 and −16 °C. Radiocarbon age estimates on skeletal material, supported by optically stimulated luminescence ages from surrounding sediments, indicate that the rhino lived around 41–43 k cal a BP. The combined geochronological, stratigraphic and palaeoenvironmental evidence places the assemblage firmly within the Middle Devensian (Marine Oxygen Isotope Stage 3). This would agree with other regional evidence for the timing of aggradation for the lowest terrace of the Trent and its tributary systems. Copyright © 2012 John Wiley & Sons, Ltd.

Fourteen novel microsatellite markers for the gopher frog, Lithobates capito (Amphibia: Ranidae) - Schyler O. Nunziata; Stephen C. Richter; Robert D. Denton; John M. Yeiser; Danielle E. Wells; Kenneth L. Jones; Cris Hagen; Stacey L. Lance (Conservation Genetics Resources, 2012)

Genome-wide analysis of copy number variants in age-related macular degeneration - Kacie J. Meyer; Lea K. Davis; Emily I. Schindler; John S. Beck; Danielle S. Rudd; A. Jason Grundstad; Todd E. Scheetz; Terry A. Braun; John H. Fingert; Wallace L. Alward; Young H. Kwon; James C. Folk; et al. (Human Genetics, 2011)

Influence of tree shelters on seedling success in an afforested riparian zone - Danielle M. Andrews; Christopher D. Barton; Stephen J. Czapka; Randall K. Kolka; Bernard W. Sweeney (New Forests, 2010)

Fine mapping of familial prostate cancer families narrows the interval for a susceptibility locus on chromosome 22q12.3 to 1.36 Mb - Bo Johanneson; Shannon K. McDonnell; Danielle M. Karyadi; Scott J. Hebbring; Liang Wang; Kerry Deutsch; Laura McIntosh; Erika M. Kwon; Miia Suuriniemi; Janet L. Stanford; Daniel J. Schaid; Elaine A. Ostrander; et al. (Human Genetics, 2008)